Part 1: Active learning and intercultural competence: Action research reform of a US study abroad programme in Seville, Spain. Issue 3 (1st December 2019) - Infante Mora, Eva; Greenwood, Davydd J.
Abstract : CASA-Sevilla is a study abroad programme for US university students with an advanced level of Spanish. In recent years, new patterns of social behaviour among students (mainly the use of technology and low-cost flights) aggravated their difficulties in establishing contacts with the local society, which often resulted in the perpetuation of stereotypes. The programme goals of cultural immersion and language improvement were therefore at risk. Through an action research and a participatory organisational development process, CASA-Sevilla stakeholders carried out a profound reform of the programme, based on the principles of active pedagogy, mentoring and community-engaged learning. This section illustrates this reform process, with its highlights and shadows.